Exploring Factors Shaping Patients’ Intentions to Adopt Cancer Management Apps: An Extended UTAUT Approach - Li, Churong (Scholar: Human Sciences, 2025)
Purpose: This study aimed to identify the determinants of cancer patients’ behavioral intention to use cancer management applications based on the Extended Unified Theory of Acceptance and Use of Technology Model and other expanded variables. Research Design, Data, and Methodology: 500 adult cancer patients treated at Sichuan Cancer Hospital were surveyed using the Web-based survey tool. They were familiar with mobile applications but had no experience in using them for cancer management. The index of the–item-objector congruence (IOC) method was used for the pretest, and the Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) were finally used to analyze the data. Results: The results showed that perceived disease threat (β=0.235, t=4.685), social influence (β=0.231, t=4.316), and performance expectancy (β=0.231, t=4.154) had a positive direct effect on patients’ behavioral intention to use mobile health applications for cancer management. What is more, perceived disease threat and social influence indirectly affected behavior intention mediated by performance expectancy. However, effort expectancy, facilitating condition, trust, and privacy showed no causal relationship with behavioral intention toward mobile health applications for cancer management. Conclusions: Further research is needed to investigate additional mobile health acceptance factors. Additionally, system developers of mobile health applications for cancer management should focus on improving performance expectancy.